Comparison of Mean Duration of Postoperative Analgesia Between Ultrasound-Guided Quadratus Lumborum Block and TAP Block in Patients Undergoing Cesarean Section - Asif Hussain, Asifa Majid, Azra Rashid, Samra Zia, Zaigham Din Baloch, Samina (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Effective analgesia after cesarean section is vital for maternal comfort, early mobilization, and breastfeeding. Regional blocks such as transversus abdominis plane (TAP) and quadratus lumborum (QL) blocks are increasingly used when neuraxial morphine is not feasible. Objectives: To compare the mean duration of postoperative analgesia between ultrasound-guided QL block and TAP block in patients undergoing elective cesarean section. Study Design & Setting: A randomized controlled trial was conducted at anesthesia department PUMHS Nawabshah. Methodology: One hundred and twenty ASA I–II parturients aged 18–40 years scheduled for cesarean section under spinal anesthesia were randomized into two groups (n=60 each). Group Q received bilateral ultrasound-guided QL block, and Group T received bilateral TAP block at the end of surgery using 20 mL 0.25% bupivacaine per side. The primary outcome was mean duration of postoperative analgesia (time to first rescue analgesic). Secondary outcomes included visual analogue scale (VAS) pain scores at rest and on movement, total rescue analgesic requirement, and adverse events. Data were analyzed using t-test and chi-square test with p<0.05 considered significant. Results: The mean duration of analgesia was significantly longer in Group Q (628.4 ± 95.6 min) than in Group T (472.1 ± 88.7 min, p<0.001). Group Q had lower VAS scores at 6, 12, and 24 hours both at rest and on movement. Total paracetamol and tramadol consumption were significantly lower in Group Q. Adverse events were minimal and comparable between groups. Conclusion: Quadratus lumborum block provided superior and longer postoperative analgesia with reduced opioid requirements compared to TAP block, without increased complications. Keywords: Analgesia, Cesarean section, Opioid-sparing, Quadratus lumborum block, TAP block, Ultrasound-guided regional anesthesia